Uma gramática perdida nos trópicos: um manuscrito setecentista sobre a Língua Geral do Brasil - Jesuita, Cristiano Silva (2020)
This thesis has as its theme of investigation the work of grammatical description carried out by the missionaries in the Brazilian colonial period. Thus, this work proposes to analyze an anonymous manuscript produced in the 18th century (1750) in the former state of Maranhão and Grão-Pará: the Gramatica da lingua geral do Brazil. Our overall goal it is contribute for the study of the history of grammar in the Brazilian colonial period through the analysis of a work that, due to the difficulty of access, has not yet received the proper attention of linguists and language historians. Among the specific objectives we highlight: to analyze grammar, taking into account the context of colonization and catechization in which the work is inserted and to compare the grammar analyzed with the Arte da Lingua Brasilica (1621), by Luís Figueira, to find out to what extent the anonymous author used the Jesuit's work to compose his work. Withregard to the theoretical foundation, we propose the approximation of the theoretical and methodological assumptions of the History of Ideas Linguísticas (AUROUX, 2009) and the Historiography of Missionary Linguistics (ZIMMERMANN, 2004, 2018; ZWARTJES, 2012), because, as we believe, the approximation of the two lines of research allows a better understanding of our object of analysis. The result of the analysis pointsout, on the one hand, the close relationship between the Gramatica da lingua geral do Brazil and the Arte da Lingua Brasilica and, on the other, the missionary's concern to describe the language in use, recording the changes and variations that occurred in the general Amazonian language of the eighteenth century